No Association between Upstream Transcription Factor 1 Gene (USF1) 306 G > A Variant and Homocysteine Levels among Bidayuh Ethnic Groups in the Sarawak Population - Mohd Aminudin, Mustapha; Sim, Sai Peng (Japan University of Health Sciences & Japan International Cultural Exchange Foundation (JICEF), 2024)
Objective: This study aimed to determine the allele and genotype frequencies of the USF1 306 G > A polymorphism and its association with homocysteine levels and lipid profiles in the Bidayuh ethnic group. Material and Methods: A total of 140 individuals from the Bidayuh ethnic group participated in this study. Genotyping was performed using Allele-Specific Polymerase Chain Reaction (AS-PCR). The association between genotype frequencies and clinical profiles was assessed using One-Way ANOVA, while Independent Sample T-tests were employed to analyze the association between allele frequencies and clinical profiles. Results: Our findings revealed that genotype and allele frequencies of the USF1 306 G > A polymorphism were not associated with homocysteine levels among the Bidayuh ethnic group. Conclusion: Therefore, our results suggest that the genetic diversity of the USF1 gene and its alleles do not influence susceptibility to elevated homocysteine levels in the Bidayuh ethnic group of the Malaysian population.